A review of the Evaluation Indicators of Post-Graduate Training in Spain - Ferrándiz, Javier Caballero (Revista Aval, 2021)
The indicators are the backbone of an evaluation. Taking into account the different models of evaluation of postgraduatetraining in Spain, in the following work a review of the evaluation indicators is carried out according to their elements and technicalaspects. For this, a brief theoretical review will be made of some of the different proposals found around the evaluation of postgraduatetraining, and more generally the evaluation methods focused on processes and those that focus on results. Subsequently, a descriptiveanalysis of the different evaluation designs of postgraduate training in Spain is carried out: both the ANECA, as well as the UniversityRankings and the Master of Evaluation (UCM), according to their different elements that comprise it.